Genome edited wheat- current advances for the second green revolution - Awan, Muhammad Jawad Akbar; Pervaiz, Komal; Rasheed, Awais; Amin, Imran; Saeed, Nasir A.; Dhugga, Kanwarpal S.; Mansoor, Shahid (Elsevier, 2022)
Common wheat is a major source of nutrition around the globe, but unlike maize and rice hybrids, no breakthrough has been made to enhance wheat yield since Green Revolution. With the availability of reference genome sequence of wheat and advancement of allied genomics technologies, understanding of genes involved in grain yield components and disease resistance/susceptibility has opened new avenues for crop improvement. Wheat has a huge hexaploidy genome of approximately 17 GB with 85% repetition, and it is a daunting task to induce any mutation across three homeologues that can be helpful for the enhancement of agronomic traits. The CRISPR-Cas9 system provides a promising platform for genome editing in a site-specific manner. In wheat, CRISPR-Cas9 is being used in the improvement of yield, grain quality, biofortification, resistance against diseases, and tolerance against abiotic factors. The promising outcomes of the CRISPR-based multiplexing approach circumvent the constraint of targeting merely one gene at a time. Deployment of clustered regularly interspaced short palindromic repeats (CRISPR)-associated (Cas) 9 endonuclease (CRISPR-Cas9) and Cas9 variant systems such as cytidine base editing, adenosine base editing, and prime editing in wheat has been used to induce point mutations more precisely. Scientists have acquired major events such as induction of male sterility, fertility restoration, and alteration of seed dormancy through Cas9 in wheat that can facilitate breeding programs for elite variety development. Furthermore, a recent discovery in tissue culturing enables scientists to significantly enhance regeneration efficiency in wheat by transforming the GRF4-GIF1 cassette. Rapid generation advancement by speed breeding technology provides the opportunity for the generation advancement of the desired plants to segregate out unwanted transgenes and allows rapid integration of gene-edited wheat into the breeding pipeline. The combination of these novel technologies addresses some of the most important limiting factors for sustainable and climate-smart wheat that should lead to the second “Green Revolution” for global food security.